(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of increasing export potential and enhancing the competitiveness of products in the agribusiness sector. The study examines the economic importance of exporting agricultural products to international markets, existing problems and mechanisms for their elimination. Also, the introduction of modern agrotechnologies in production, bringing product quality to international standards, improving the logistics system, developing marketing strategies and state support measures are justified as important factors for increasing export volumes. The article highlights the possibilities of achieving sustainable development of the national economy by strengthening the competitiveness of agribusiness entities in foreign markets.